Exploring students' demotivation and remotivation in learning English. (December 2021) - Wang, Shufang; Littlewood, William
Abstract: This study combined collaborative tasks with qualitative research procedures in order to explore what factors students had experienced as demotivating in their English learning and their suggestions for remedying them. It was conducted with an intact class of 40 advanced learners of English (mostly future teachers) following a Masters course. In the first stage of the study, the motivational change graph of Song and Kim (2017) was used to stimulate learners to chart the development of their motivation over successive stages of their learning career and to reflect on reasons for significant fluctuations (downwards or upwards). The results served as the subject of peer interviews and brief class reports on individual participants' experiences. In the second stage, prepared with these reflections, participants were asked to focus on their past classroom experience, as well as that of other students they had known. Using the collaborative learning technique of forward snowball, participants were first asked to brainstorm and list all factors they could think of which might lead to demotivation in English learning. This was followed by a reverse snowball stage which required deeper reflection and critical thinking. In groups of 4 or 5, participants were asked to analyze and decide (a) what they regarded as the five most important demotivational factors in language learning and (b) what pedagogical strategies might be effective in remedying them. Results were combined into a class profile. This stage also served to bridge the transition in the course from a series of classes that had focused mainly on learning to one which would focus mainly on pedagogy. The experience (with others) was also intended to contribute to the students' 'experiential knowledge' of task-based learning in preparation for their future work as teachers.